2021
DOI: 10.1371/journal.pone.0250465
|View full text |Cite
|
Sign up to set email alerts
|

Community knowledge, attitude and practices to SARS-CoV-2 disease 2019 (COVID-19): A cross-sectional study in Woldia town, Northeast Ethiopia

Abstract: SARS-CoV-2 disease 2019 (COVID-19) is pandemic and currently becomes a serious cause of death worldwide. It is caused by a SARS-CoV-2 belonging to a family known as corona virus. The aim of this study is to assess the community knowledge, attitude and practice strategy implementation on SARS-CoV-2 disease 2019 (COVID-19). A cross-sectional survey study was done from July to October, 2020 in Woldia town, Northeast Ethiopia. Interviewer-administered questionnaire was used to collect data from 404 respondents. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…The little knowledge of disease, negative or casual approach and dangerous practices were the reasons for the spread of COVID-19 infection and subsequent outbreak propagation [16]. The knowledge, attitude, and practices of the community studied in Ethiopia regarding COVID-19 and results revealed that 53.7% of respondents had a negative attitude towards the COVID-19 pandemic [17]. The negative or casual approach of the communities and the relatively disadvantageous categories of society pose a social challenge as they underestimate the COVID-19 risk and keep themselves unaware of symptoms [18].…”
Section: Introductionmentioning
confidence: 99%
“…The little knowledge of disease, negative or casual approach and dangerous practices were the reasons for the spread of COVID-19 infection and subsequent outbreak propagation [16]. The knowledge, attitude, and practices of the community studied in Ethiopia regarding COVID-19 and results revealed that 53.7% of respondents had a negative attitude towards the COVID-19 pandemic [17]. The negative or casual approach of the communities and the relatively disadvantageous categories of society pose a social challenge as they underestimate the COVID-19 risk and keep themselves unaware of symptoms [18].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) reported the first outbreak of the coronavirus disease-2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), in December 2019 [ 1 , 2 ]. SARS-CoV-2, which broke out in 2019, has become a major public health problem worldwide, causing great fear in people and is still ongoing as a pandemic in 2021 [ 2 , 3 ]. However, since the outbreak of H1N1 influenza in 2009, health-related ministries in each country have been paying special attention to preparing strategies to prepare for a pandemic and prevent its spread [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beliefs therefore matter in health behavior, [9][10][11] including with Covid-19. [3][4][5][6][7][8] Beyond beliefs, the sociodemographic characteristics of the study population fur- Mask usage was more prevalent among respondents who were females, married, who had tertiary education, earned a minimum of N50,000 per month, and lived in rural Nigeria. Some studies have also shown this association elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 While the literature is replete with evidence to show that attitude and behaviour, encapsulated in health beliefs, matter for the spread of infectious diseases, studies have further confirmed same to be valid with Covid-19. [3][4][5][6][7][8] Individuals, according to the health belief model (HBM), prevent or expose themselves from/to diseases based on their perception of their susceptibility, the severity of the disease, benefits accruable from engaging in protective behaviour, barriers to the protective behaviour, factors that could lead them to adopting the protective behaviour, and their perceived efficacy of the protective action. [9][10][11] Given the freedom to choose therefore, individuals may engage in health behaviour that put them and others at risk of infection.…”
Section: Introductionmentioning
confidence: 99%